Comparative efficacy of passive and mechanical fan-pad cooling system for microclimate modification and welfare in broiler production - CHIB, S S; SHARMA, A; SINGH, Y; SETHI, A P S; SAINI, A L; SINGH, C (The Indian Journal of Animal Sciences, 2016)
Efficacy of passive cooling vis-à-vis mechanical fan-pad cooling system was assessed for microclimate modification to alleviate heat stress and improving growth performance and welfare of broilers. Cooling treatments comprised of Tc (control without any cooling system), TJSC passive cooling (jute sheet roof shading and curtains with gravity flow sprinklers), TGSC passive cooling (green sheet roof shadings and curtains with gravity flow sprinklers) and TFP (fan pad mechanical cooling systems). The results of shed microclimate indicated that maximum ambient temperature, temperature humidity index (THI) and duration and level of heat stress in control were significantly higher than passive (TJSC and TGSC) and mechanical (TFP) cooling group. Growth performance and feed efficiency, in both passive (TJSC and TGSC) and mechanical cooling (TFP) were significantly better than control. However, growth performance and feed efficiency of chicks was significantly higher in TFP than chicks in passive (TJSC and TGSC) cooling groups. In passive cooling systems (TJSC and TGSC), the plasma catalase, glutathione peroxidase (GPx) and BUN were significantly lower than control (Tc) but significantly higher than mechanical cooling (TFP) system. The stress related behavioural activities, panting, preening, scratching and wing flapping were significantly higher in control as than in cooling system. It was concluded that passive cooling system can be an environment friendly and energy independent alternate to intensive mechanical cooling system to reduce heat stress and improve growth and welfare in broiler production.